2008
DOI: 10.1007/s11814-008-0108-0
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic effects of potassium on lignin steam gasification with γ-Al2O3 as a bed material

Abstract: The effects of potassium on the reactivity of biomass-char steam gasification with the presence of a porous material were investigated by using a thermogravimetric reactor with high-heating rates. Lignin was employed as a char-rich biomass model compound. The potassium carbonate (K 2 CO 3 ) was added to lignin and a mixture of lignin and γ-Al 2 O 3 porous particles by means of aqueous impregnation. The effects of K 2 CO 3 and γ-Al 2 O 3 addition on pyrolysis of lignin and steam gasification of lignin-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Moreover, the addition of 0.7 wt% Na and K increased the molar percentages of H 2 from 12% to 23.6% and from 12% to 29%, respectively. Kuchonthara, Vitidsant, and Tsutsumi (2008) found a trend similar to that of Lin et al (2013) when they used K 2 CO 3 as the bed material for lignin gasification. K 2 CO 3 also promoted the conversion of tars, resulting in higher carbon conversion efficiency.…”
Section: Effect Of Catalystssupporting
confidence: 60%
“…Moreover, the addition of 0.7 wt% Na and K increased the molar percentages of H 2 from 12% to 23.6% and from 12% to 29%, respectively. Kuchonthara, Vitidsant, and Tsutsumi (2008) found a trend similar to that of Lin et al (2013) when they used K 2 CO 3 as the bed material for lignin gasification. K 2 CO 3 also promoted the conversion of tars, resulting in higher carbon conversion efficiency.…”
Section: Effect Of Catalystssupporting
confidence: 60%
“…In addition, seaweed has high ash content which contains larger amount of alkali and alkaline earth species than land-based biomass [21,22]. It is well known that the gasification activity of carbon in carbonaceous materials can be greatly enhanced by various alkali and alkaline earth metal compounds [23][24][25][26][27][28]. Several studies also indicated that alkali and alkaline earth species such as K and Ca play a key role in the formation of active sites for the surface carbon gasification reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also indicated that alkali and alkaline earth species such as K and Ca play a key role in the formation of active sites for the surface carbon gasification reaction. It can reduce tar production by means of either stopping tar formation initially or by catalyzing tar decomposition and decreasing the formation of char [27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a small addition of alkali chlorides accelerated the release of small-molecule gases during biomass pyrolysis [28]. In addition, the addition of K might promote the reforming of hydrocarbons [24], which can contribute to the production of H2 through reforming reactions. And similar phenomenon was found by Wang et al [47,48], they studied the effect of alkali metal on the catalytic reforming of bio-oil.…”
Section: 2mentioning
confidence: 99%
“…Patwardhan et al [22] studied the biomass ash and discovered that the major constituents in biomass ash are silica, potassium, calcium, magnesium and sodium, and potassium occupies a large proportion in addition to silica. The alkali metals including potassium have been reported to largely affect biomass gasification process in terms of product yield [23,24]. In general, the presence and release of alkali metals have impacts on both primary biomass pyrolysis and the secondary reforming reactions [25][26][27].…”
Section: Introductionmentioning
confidence: 99%